Proceedings of the 2015 Information Technology and Mechatronics Engineering Conference 2015
DOI: 10.2991/itoec-15.2015.17
|View full text |Cite
|
Sign up to set email alerts
|

Seam the Real with the Virtual:a Review of Augmented Reality

Abstract: Abstract. In this paper, we reviewed several outstanding contributions over the past decade in the field of augmented reality. The papers are selected according to their citation rate in the academic resources of Google scholar. In addition, considering that augmented reality covers several topics, and it has intersection with pervasive computing and wearable computing in concept, only the promising technologies and some prominent cases are concerned. In our opinion, a typical AR application is a solution for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Then, [15] show how The virtual lab in physics learning assists students in better understanding the material's structure. According to [30], virtual reality is a renewable creation that makes school and college learning more interesting and engaging. It will be fascinating for the students.…”
Section: Discussionmentioning
confidence: 99%
“…Then, [15] show how The virtual lab in physics learning assists students in better understanding the material's structure. According to [30], virtual reality is a renewable creation that makes school and college learning more interesting and engaging. It will be fascinating for the students.…”
Section: Discussionmentioning
confidence: 99%
“…showed if virtual laboratories for education in science, technology, and engineering, this product is very important to improve the knowledge student [10], and then seam the real with the virtual: a review of augmented reality showed students very happy to learn with virtual reality. [11], so the recent developments in game-based virtual reality educational laboratories make students can study with games every lesson in the class [11], and then the impact of the virtual laboratory on students' attitude in a general physics laboratory is very significant about 60% student have good attitude to goal material [12], so virtual reality for learning fish types in kindergarten make a student happy with material fish with animation product [13], finally exploring chemistry using virtual instrumentation-challenges and successes for the student to get good knowledge about chemistry material [14].…”
Section: Authors' Contributionsmentioning
confidence: 99%
“…In making SD thematic textbook products based on augmented reality, grade 1 material has been made in a team by the UT research team and assisted by IT experts outside UT so that there is good collaboration with the UT research team to create a material framework and design that is expected in making elementary thematic materials based on AR, then executed by IT experts who are competent in their fields, after the design of the AR-based elementary thematic textbooks took approximately 3 months according to the advice from the results of the first year research, the product was continued in the third stage, namely development [10]. learning strategies used in delivering personal material [11]. In this development stage, the framework that has been designed will be realized so as to produce a product that can be implemented.…”
Section: Designmentioning
confidence: 99%